Web-Based Interactive Virtual Tour as an Information Media and Introduction to Post-Pandemic Lecture Buildings at Universitas Lampung - Panji Kurniawan; Nugroho Ifadianto; Agung Cahyo Nugroho (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
This study aims to determine the effectiveness of architectural communication methods using a link embedded in online media or social media. This research method is an interactive communication simulation in the form of a Virtual Tour using the 360o panoramic image method. A 360o panoramic image is multiple images combined to get a wider, more detailed image. Panorama images will be set using software and then uploaded to a website's database. The public, in this case more concerned with the academic community, can easily get information about the shape of buildings and spaces from various predetermined points, without installing certain 3D Architecture software. It is enough to use a computer or smartphone based on iOS or Android and without using object tracking or the like to activate communication, because it is web-based, it can be easily accessed anywhere and anytime as long as the user has the intended link. This is an alternative media in providing information about the object, which in this case is the Lecture Building to the public, especially students and parents during the post-pandemic period.